Significant advances in primary and vocational education: Social inclusion and the transformation of students through the Urban Projovem program in the City of Manaus, Amazonas State, Brazil (Research, Society and Development, 2024)
The objective of this research is to reflect on elementary and professional education, inclusion and transformation in the lives of young people in the Projovem Urbano Program in the city of Manaus-Am. The work presents the experience of students participating in social inclusion, considering their upbringing context related to high school dropout rates, a high number of young people who were unable to complete their elementary or professional education, and the students who participate in the program are excluded from society. Methodology: this is a qualitative research and case study. It was found that young people need help and need to be trained to exercise their citizenship, the difference in this program is to seek lost time, to be able to recover through schooling and professional education the changes in the lives of students. Thus, it was observed that Projovem Urbano is a national policy aimed at young people aged 18 to 29, who did not complete their studies and who are in poverty, it offers the possibility for young people to complete their elementary education, in a proposal that will benefit students for the professional job market. The research seeks to reflect on the challenges that lie not only in the results for the young people benefiting from Projovem, but mainly in the implementation and construction of the program itself.